Fracture behavior, marginal gap width, and marginal quality of vented or pre‐cemented CAD/CAM all‐ceramic crowns luted on Y‐TZP implants. Issue 2 (31st October 2017) - Zaugg, Lucia K.; Meyer, Simon; Rohr, Nadja; Zehnder, Isabella; Zitzmann, Nicola U.
Abstract: Objectives: To investigate the fracture behavior and marginal gap region of CAD/CAM fabricated lithium disilicate (L) and zirconium dioxide (Z) crowns using palatal venting (PV), pre‐cementation with custom analogs (CA), or conventional cementation technique (SP) with adhesive cement (A) or resin‐modified glass ionomer cement (B). Material and methods: Twelve groups ( n  = 6) were set according to material (L, Z), cement (A, B), and technique (PV, CA, SP). Specimens were thermo‐mechanical aged (TML), loaded until fracture (LF) and fracture patterns recorded. Marginal gap width and quality were assessed and compared to replicas obtained before and after TML. Results: Crown material significantly influenced LF with a mean of 1037.6 ± 282.4 N in L and 5356.3 ± 1207.0 N in Z groups ( p  <   .001). Neither cement material nor cementation method affected the outcome. Fractures occurred along the mesial‐distal central fissure in both materials. Gap width before TML was 22.04 ± 13.42 μm for L and 19.98 ± 12.72 μm for Z specimens, with overall no influence of crown material, cement type, or method. Marginal cleanliness just below the polished implant shoulder reached 66.7%–88.9% with A, and 91.7%–100% with B, and tended to increase in all groups during TML indicating a decrease in excess cement. Implant‐crown junctions were cleaner with B compared to A ( p  ≤   .001) and along Z crown surfaces compared to L ( p  ≤   .007). Conclusions: Crown venting of lithium disilicate and zirconium dioxide crowns did not affect the fracture load and patterns. Complete cement removal was rare, and the observed particle ablation requires further clinical attention, particularly with submucosal margins.